Aproximación a la historiografía de la masonería latinoamericana - Ferrer Benimeli, José Antonio (2012)
Masonic Latin American historiography is undergoing a methodological regeneration therefore it is necessary to add new research to the references outlined in previous publications. This paper is divided into two parts. The first one discusses by Latin American country the principal works on the History of Freemasonry that have been published. The comment is based on both the works that offer a scientifically acceptable level (minority) and those without it (the majority). The second part is devoted to reporting the references. It must be emphasized that is an open whose completeness is as complex as large geographical extent addressed. Therefore, just wants to be a point of reference on completing this historiography will continue in the future.